2018
DOI: 10.1007/s40199-018-0223-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective, antidiabetic and antioxidant effect of Hedera nepalensis and lupeol against STZ + AlCl3 induced rats model

Abstract: Purpose This study was aimed to evaluate the effect of Hedera nepalensis crude extract (HNC) and its isolated compound lupeol on antioxidant defence system, biochemical parameters and behavioural indices of Alzheimer disease generated in diabetic rats. Methods To evaluate the effect of the plant extract and lupeol, symptoms of Alzheimer and diabetes were induced in rats by STZ + AlCl 3 treatment. Glucose level was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 56 publications
2
34
0
3
Order By: Relevance
“…Similar results have been reported when chrysin [108] or Andrographis paniculata extract [175] are administered to STZ-treated rats. Similar outcomes have been reported when Hedera nepalensis extract is administered to STZ-aluminium trichloride rat model [176]. Likewise, grape seed proanthocyanidin extract [177], kola nut extract [178] or Garcinia kola seeds [155] also improve cognitive impairment in diabetic rat models.…”
Section: Natural Compounds and Central Complications In Dmsupporting
confidence: 60%
“…Similar results have been reported when chrysin [108] or Andrographis paniculata extract [175] are administered to STZ-treated rats. Similar outcomes have been reported when Hedera nepalensis extract is administered to STZ-aluminium trichloride rat model [176]. Likewise, grape seed proanthocyanidin extract [177], kola nut extract [178] or Garcinia kola seeds [155] also improve cognitive impairment in diabetic rat models.…”
Section: Natural Compounds and Central Complications In Dmsupporting
confidence: 60%
“…Hashmi et al (2018) demonstrated that treatment of type 3 diabetes rats associated with Alzheimer disease (induced with STZ + AlCl 3 ) with crude extract of H. nepalensis causes improvement of learning and memory during MVM test elevated plus maze tests. In addition, decreased blood glucose and oxidative stress confirmed by increase in CAT and SOD levels in the liver and brain tissues were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Trên thế giới, loài này phân bố hẹp ở các nước châu Âu, dãy Himalaya và một số nước châu Á trong đó có một số tỉnh miền núi phía Bắc tại Việt Nam [2]. Các nghiên cứu gần đây phát hiện trong Dây thường xuân chứa nhiều nhóm chất như: saponin, alkaloid, tanin, terpenoid, các hợp chất phenolic [3] saponin A ức chế tế bào ung thư [4], lupeol ức chế dipeptidyl peptidase-4 cho tiềm năng chữa bệnh đái tháo đường [5][6][7], các hợp chất phenolic có khả năng chống oxy hóa, bảo vệ tế bào thần kinh [5]. Ngoài ra, Dây thường xuân cũng được chứng minh có nhiều tác dụng khác như giảm đau, kháng viêm, chống trầm cảm và chống đông máu [8].…”
Section: Mở đầU *unclassified